Os pressupostos de uma ética das virtudes na filosofia de Alasdair MacIntyre: práticas, narrativa de vida e tradição. - Fontenele, Thaline Luize Ribeiro (2012)
This present research aims to understand and stimulate the debate around virtue ethics in philosophy of Alasdair MacIntyre. To this Scottish philosopher, the contemporary society has been facing a serious morality crisis, which reflects majorly in social and psychological conflicts of the contemporary human being .The existence of such moral crisis is justified by an absence of a teleological character which can substantiate these subject s actions. Without a telos , human beings start substantiating their actions in personal emotions and desires, letting themselves be driven by emotionalism. Thus, considering the argumentative process of MacIntyre in major writings as: After virtue (2001), Whose Justice? Which Rationality? (1991), Three Rival Versions of Moral Inquiry (1999), the work claims to present the moral presuppositions of his thoughts, contrasting the concepts of practical, life narrative and tradition, offering the necessary basis not only to understand the existence of such moral crisis, but, also able to recover the teleological character consistent with social context of contemporary society. Therewith, it s expected to conclude that the liberal culture cannot provide a last end to human act and virtue ethics of Alasdair MacIntyre can be a satisfying proposal to solve the moral conflicts of this society.